1992
DOI: 10.1073/pnas.89.7.2732
|View full text |Cite
|
Sign up to set email alerts
|

Expression cloning of a common receptor for parathyroid hormone and parathyroid hormone-related peptide from rat osteoblast-like cells: a single receptor stimulates intracellular accumulation of both cAMP and inositol trisphosphates and increases intracellular free calcium.

Abstract: Parathyroid hormone (PTH), a major regulator of mineral ion metabolism, and PTH-related peptide (PIHrP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
544
0
9

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 936 publications
(572 citation statements)
references
References 32 publications
14
544
0
9
Order By: Relevance
“…(50) It has also been reported that PTHrP activates PTH-R1 in relation to the homology of its NH 2 -terminal domain with PTH and that receptor stimulation by the PTHrP subunit (aa 1-40) results in both intracellular PKA and PKC activation. (2) We confirmed the PTH-R1 sensitivity to PTHrP in MM cells and demonstrated that the receptor is specifically susceptible to the NH 2 -terminal fragment (aa 1-40) because, in all instances, we recorded an increased influx of Ca 2þ and cAMP content. This bioactivity was not observed using the mid-region fragments, even those including NLS, nor using osteostatin, whose receptor has not yet been identified.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…(50) It has also been reported that PTHrP activates PTH-R1 in relation to the homology of its NH 2 -terminal domain with PTH and that receptor stimulation by the PTHrP subunit (aa 1-40) results in both intracellular PKA and PKC activation. (2) We confirmed the PTH-R1 sensitivity to PTHrP in MM cells and demonstrated that the receptor is specifically susceptible to the NH 2 -terminal fragment (aa 1-40) because, in all instances, we recorded an increased influx of Ca 2þ and cAMP content. This bioactivity was not observed using the mid-region fragments, even those including NLS, nor using osteostatin, whose receptor has not yet been identified.…”
Section: Discussionsupporting
confidence: 74%
“…(1) These peptides show high homology within their NH 2 -domain in the 1-34 amino acid (aa) sequence, by which they bind the same G-protein receptor (PTH-R1). (2,3) During fetal development PTHrP is produced by perichondral cells to adjust placental calcium levels and support the differentiation of endochondral cells to chondrocytes, (4,5) whereas after birth it concurs to development of mammary glands and lactation. (6) The predominant activity of PTHrP in bone metabolism has been definitely proved in homozygous PTHrP-deficient mice that show abnormal bone morphogenesis, leading to osteopetrosis and short-term survival after birth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of cytokines, such as 1,25-dihydroxyvitamin D3, dexamethasone, interleukin 1b, and transforming growth factor b1 have been found to upregulate aromatase expression at the transcriptional level (Ribot et al, 2006). Parathyroid hormone, clinically used to increase bone formation and bone mass in the treatment of osteoporosis, promotes osteoblast proliferation and differentiation by stimulating intracellular cAMP production (Abou-Samra et al, 1992). cGMP and its activated PKG have also been found to regulate osteoblast proliferation and differentiation (Rangaswami et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…PTH and PTHrP bind to the same cell-surface receptor (the type 1 PTH/PTHrP receptor) (Abou-Samra et al, 1992), and PTHrP exerts many effects on target cells in common with PTH, including elevation of intracellular cAMP (Birch et al, 1995) and [Ca2+], (Donahue et al, 1988;Schofl et al, 1991). PTHrP has been localized to a range of normal and fetal tissues (Moniz et al, 1990), but its physiological role is not yet clear.…”
mentioning
confidence: 99%